BASIC LEADERSHIP TRAINING TO ENHANCE PUBLIC SPEAKING SKILLS, LEADERSHIP AND MOTIVATION AMONG STUDENT COUNCIL MEMBERS - Maria Keisya Mbete; Maria Hesliana Gowe; Maria Jesika Nuhut; Hamsa Doa; Adrianus Nasar; Yasinta Embu Ika; Natalia Peni (LPPM Universitas Flores, 2026)
This community service program aimed to improve the public speaking, leadership, and motivation of student council administrators at State Senior High School 1 of West Riung, East Nusa Tenggara, Indonesia, through Basic Leadership Training. The student council administrators faced several challenges, including low self-confidence in public speaking, limited leadership skills, insufficient motivation to organize, and a lack of experience managing school organizational activities. The program was implemented in three stages: preparation, implementation, and evaluation. During the preparation stage, participant needs were identified through observation, coordination with the school was conducted, and training materials were developed. The implementation stage consisted of lectures, group discussions, simulations, speech practices, ice-breaking activities, and leadership games. The training materials focused on public speaking, leadership, organizational motivation, and teamwork. The evaluation process involved observing participant engagement, administering response questionnaires, and assessing public speaking performance. The results demonstrated that the training program effectively increased participants’ confidence in speaking before an audience, enhanced their leadership skills in managing groups and discussions, and strengthened their motivation to implement organizational programs within the school. Throughout the activities, participants showed greater enthusiasm, active participation, self-confidence, and collaboration skills. The positive responses and high level of engagement indicated that the training provided a meaningful learning experience for the student council administrators. Therefore, Basic Leadership Training can serve as an effective approach to fostering communicative, disciplined, responsible, and leadership-oriented student character within school organizations.